PENGARUH ARUS KAS OPERASI DAN LABA AKUNTANSI TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan LQ – 45 di Bursa Efek Indonesia Periode 2016 – 2019) - Khoirunnisa Cahya Firdarini; Kunaidi Kunaidi (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2022)
This research aims to determine the effect of operational cash flow and accounting earnings to the stock return both partially and simoultantly. Population in this study are LQ45 firms for 2016-2019 period and the sample was selected through purposive sampling. Based on classic assumptiont test, we have 100 total sample. Data analysis technique used is multiple regression analysis. The result of this study indicate that (1) operational cash flow not have significant effect to the stock return, (2) accounting earnings have positive and significant effect to the stock return and (3) operational cash flow and unting earnings have positive and significant effect to the stock return simoultantly.